2012
DOI: 10.1037/a0023062
|View full text |Cite
|
Sign up to set email alerts
|

PTSD in depressed mothers in home visitation.

Abstract: Recent research has suggested that mothers participating in home visitation programs have a high incidence of mental health problems, particularly depression. Posttraumatic stress disorder (PTSD) is a common comorbidity with depression, yet its prevalence among home visiting populations and implications for parenting and maternal functioning have not been examined. This study contrasted depressed mothers with (n = 35) and without PTSD (n = 55) who were enrolled in a home visitation program. Results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 57 publications
1
35
2
Order By: Relevance
“…Those with comorbid depression/PTS also reported elevated levels of inconsistent discipline; however, their self-reported discipline inconsistencies were not as high as those caregivers with depression or PTS alone and did not differ significantly from other groups. This is inconsistent with findings of research with mothers with PTS and/or depression related to interpersonal violence, which indicated that having both conditions had the most problematic impact on parenting in a study of mother-infant dyads (Ammerman et al, 2012). Inconsistent discipline was the only subscale that evidenced statistically significant differences when considering child report.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Those with comorbid depression/PTS also reported elevated levels of inconsistent discipline; however, their self-reported discipline inconsistencies were not as high as those caregivers with depression or PTS alone and did not differ significantly from other groups. This is inconsistent with findings of research with mothers with PTS and/or depression related to interpersonal violence, which indicated that having both conditions had the most problematic impact on parenting in a study of mother-infant dyads (Ammerman et al, 2012). Inconsistent discipline was the only subscale that evidenced statistically significant differences when considering child report.…”
Section: Discussioncontrasting
confidence: 87%
“…There is emerging evidence that the combined impact of depression and PTS on parenting is more detrimental than either condition alone (Ammerman, Putnam, Chard, Stevens, & Van Ginkel, 2012). Yet, to date, few studies have examined this interplay, so we look to the current literature regarding the relation of parenting to each condition independently.…”
Section: Parenting In the Context Of Caregiver Posttraumatic Stress Amentioning
confidence: 99%
“…In addition, due to the small sample size, we limited our analyses to overall PTSD symptom severity and did not include reliable change by PTSD symptom cluster. Given that previous research has suggested that symptoms of emotional numbing or avoidance and hyperarousal might be most associated with and relevant to parental functioning (Ammerman et al, 2012;Gewirtz et al, 2010), it is recommended that future research investigate the associations between different PTSD symptom clusters and parenting outcomes to determine whether certain PTSD symptoms are differentially related to functioning in this domain. Furthermore, given that this study relied only on the use of self-report measures to assess parenting satisfaction and efficacy, future research would benefit from the incorporation of multimodal assessment of parenting (e.g., the use of self-report measures in combination with observational methods), as well as collateral information from children, to better understand how this construct is related to PTSD and how parental treatment for PTSD might impact this domain.…”
Section: Future Research and Limitationsmentioning
confidence: 99%
“…KEYWORDS CBCT for PTSD, cognitive-behavioral conjoint therapy for posttraumatic stress disorder, couple therapy, parenting, posttraumatic stress disorder, PTSD There are well-established associations between parental trauma and posttraumatic stress disorder (PTSD) and a variety of difficulties related to parenting (e.g., Ammerman, Putnam, Chard, Stevens, & Van Ginkel, 2012;Banyard, Williams, & Siegel, 2003;L. R. Cohen, Hien, & Batchelder, 2008;E.…”
mentioning
confidence: 99%
See 1 more Smart Citation